If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(4x + 5) = 0 Reorder the terms: -10(5 + 4x) = 0 (5 * -10 + 4x * -10) = 0 (-50 + -40x) = 0 Solving -50 + -40x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + -40x = 0 + 50 Combine like terms: -50 + 50 = 0 0 + -40x = 0 + 50 -40x = 0 + 50 Combine like terms: 0 + 50 = 50 -40x = 50 Divide each side by '-40'. x = -1.25 Simplifying x = -1.25
| 4/3x=36 | | h=-4.9t^2+14.7t+49 | | 9x-35=4x+14 | | 2-4cos(3x)=0 | | 3n=5+11 | | r/6=17 | | -6x+732=0 | | 2n=3+1 | | -8y+24=-13y-4 | | 0.0075(0.05-x)=x*x | | 5k^2=-9k+18 | | 2n=3+2 | | 9x+185=7x+156 | | 0.5(5-7x)=8-(fx+6) | | 3-3x^2=-85 | | n=3+2 | | 4x+(3+6x)=(4x+3)+6x | | 2x/5-4/3=-8/5 | | 7.5-x=4 | | X^3+4x^2+3x+45=0 | | 4w+9.6=4.8 | | 3ln(x+2)=24 | | 4x+24=72 | | (7b-5)-2(3b+2)=-2 | | (52)(53)= | | 6v=192 | | 123=1234 | | 16x^4y^4/2x^2y^4 | | 3x^3+22x-26=0 | | 17-5(x-4)=17 | | 4(4-8m)+28m=-272-4m | | -y/4=-42 |